2021
DOI: 10.1111/cei.13644
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cytokine and chemokine profiles in cerebrospinal fluid caused by the etiology of cryptococcal meningitis and tuberculous meningitis in HIV patients

Abstract: The roles of cytokines and chemokines in HIV-associated cryptococcal meningitis (HCM) and HIV-associated tuberculous meningitis (HTBM) are debatable. In sum, 34 HIV-infected patients without meningitis, 44 HCM patients and 27 HTBM patients were enrolled for study. The concentrations of 22 cytokines/chemokines in cerebrospinal fluid (CSF) were assayed at admission. Principal component analysis (PCA), Pearson's and logistic regression analyses were used to assess the role of cytokines/chemokines in HCM and HTBM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Additionally, higher levels of TNF were detected in peripheral blood mononuclear cells of patients newly diagnosed with TB compared to those with chronic refractory TB ( 20 22 ). Compared to Human Immunodeficiency Virus(HIV)–infected patients without central nervous system involvement, HIV-associated tuberculous meningitis patients exhibited elevated levels of T-helper factor (Th) 17, TNF-α, and LT ( 23 ). In the study conducted by Jing Wei et al., the Kyoto Genomic Encyclopedia and single gene enrichment analysis of peripheral blood mononuclear cells from the Asian population of Mtb-Ag stimulated and control samples revealed a significant enrichment of the TNF signaling pathway, which is closely associated with tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, higher levels of TNF were detected in peripheral blood mononuclear cells of patients newly diagnosed with TB compared to those with chronic refractory TB ( 20 22 ). Compared to Human Immunodeficiency Virus(HIV)–infected patients without central nervous system involvement, HIV-associated tuberculous meningitis patients exhibited elevated levels of T-helper factor (Th) 17, TNF-α, and LT ( 23 ). In the study conducted by Jing Wei et al., the Kyoto Genomic Encyclopedia and single gene enrichment analysis of peripheral blood mononuclear cells from the Asian population of Mtb-Ag stimulated and control samples revealed a significant enrichment of the TNF signaling pathway, which is closely associated with tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings substantiate the efficacy of LT as a predictive factor for PTB. Moreover, among individuals co-infected with HIV and TB, the utilization of inflammatory biomarker signatures successfully identified those at the highest risk for developing PTB ( 23 ). These inflammatory biomarkers reflect numerous activations of innate immunity and increased Th1 responses, which are associated with the immune response to MTB.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al. found that the expression levels of Th1, Th2, Th 17, TNF-α, and TNF-β were elevated in TBM patients compared to those without the CNS infections in HIV-infected persons ( 122 ). Moreover, the expression levels of IFN-γ, regulated upon activation normal T cells expressed and presumably secreted (RANTES) and interferon-inducible protein (IP-10) in TBM patients were higher than in non-TBM with HIV infection.…”
Section: Biological Roles Of B and T Lymphocytes In Tbmmentioning
confidence: 99%
“…Another report indicated that IL-2-positive T lymphocytes in the CSF of TBM patients can produce specific and reactive antigen when stimulated with IL-2, antigen-presenting cells (APC), or Muromonab CD3 (OKT3) antibody (121). Xu et al found that the expression levels of Th1, Th2, Th 17, TNF-a, and TNF-b were elevated in TBM patients compared to those without the CNS infections in HIV-infected persons (122). Moreover, the expression levels of IFN-g, regulated upon activation normal T cells expressed and presumably secreted (RANTES) and interferon-inducible protein (IP-10) in TBM patients were higher than in non-TBM with HIV infection.…”
Section: Biological Roles Of B and T Lymphocytes In Tbmmentioning
confidence: 99%
“…Intriguingly, these symptoms parallel those of bacterial meningitis and viral meningitis, further complicating the timely diagnostic process. In advanced disease states, the onset of neurological complications sharply exacerbates both mortality and the likelihood of lasting disability linked to TBM ( Roca et al, 2008 ; Török, 2015 ; Mezochow et al, 2017 ; Kumar et al, 2021 ; Xu et al, 2021 ). Hence, early, precise, and expedient diagnostic and therapeutic interventions are crucial to reducing the mortality associated with this condition.…”
Section: Introductionmentioning
confidence: 99%